Strategic planning based on participation principles in science-intensive subsidiaries of vertically integrated oil and gas companies - K. G. Kachalkina; D. V. Kotov (Управление)
The article considers the features of strategic planning in knowledge-intensive subsidiaries of vertically integrated oil and gas companies. Based on the analysis, it has been proposed to improve the approach to strategic planning by incorporating principles and mechanisms of participatory planning. In modern conditions, strategic development of vertically integrated oil and gas companies is closely connected with obtaining high-quality R&D work results that meet the challenges that stand in the way of successful development of the oil and gas complex. Obtaining such results is possible with competent strategic planning of science-intensive subsidiaries activities that produce main scientific results for vertically integrated oil and gas companies. The use of principles of participatory approach to industrial enterprise management at the stages of strategic planning can become one of the options for improving strategic planning quality. The existing approach to strategic planning in science-intensive subsidiaries of vertically integrated oil and gas companies has been considered, its advantages and disadvantages analyzed. It has been recommended to eliminate the identified shortcomings and thus improve the existing approach by adapting interactive strategic planning to peculiarities of vertically integrated oil companies and supplementing it with participatory mechanisms. New principles have been proposed and directions for strategic planning tools development in knowledge-intensive subsidiaries of vertically integrated oil and gas companies defined.